Historical and socio-economic characterization of a territorial strip of cassava growing in the district of La Fortuna, San Carlos and Peñas Blancas, San Ramon, North Huétar region of Costa Rica - Rodríguez-Barrientos, Francisco (2014)
This article derives from the research project “Improvement in the efficiency of the productive chain of cassava in the district of Fortune, San Carlos, Costa Rica.” The main objective of the project consisted on improving the efficiency and productivity in the various stages of the agro productive process of the cassava. The research was conducted in a strip of land covering an area of the district of La Fortuna, canton of San Carlos, Alajuela, Costa Rica, traditionally a major cassava growing production site, and an area of the district of Peñas Blancas (canton of San Ramón, Alajuela province). The strip of land selected is within the North Huetar Costa Rica. This population, connected to the production sector, processing and marketing of cassava, was the goal of the research population. The project lasted three years (2006-2008). This article makes a historical, social and economic characterization of the strip of land chosen for the research. However, the article also analyzes the economic and social consequences for the communities located in the territory studied, and the region of which they form part, derived from the national and international changes occurred, especially, in the last thirty years. Thus, we try to outline the scope and nature of any transformations in the selected band, always placing the analysis within the context of North Huetar. Subsequently articles will be published with the results obtained in the agricultural industries (maquiladoras and packing) an social stages, highlighting those matters related to the situation of workers in packing, emphasizing on the Nicaraguan migrants